2013
DOI: 10.1038/bjc.2012.546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of circulating miR-221 in plasma of patients with pancreatic cancer

Abstract: Background:Several recent studies have demonstrated that microRNAs (miRNAs) are stably detectable in plasma/serum. We tested miR-221 and miR-375, which are frequently reported to be highly and poorly expressed in pancreatic cancer (PCa), as candidates for plasma biomarkers in PCa.Methods:This study was divided into three parts: (1) Confirmation of higher miR-221 levels in primary PCa tissue and cell lines than normal pancreatic tissues. (2) Evaluation of plasma miR-221 and miR-375 concentrations by comparing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(164 citation statements)
references
References 47 publications
4
159
1
Order By: Relevance
“…Moreover, compared to serum, plasma might retain higher protein levels, including those of coagulant-related proteins. These finding prompt us to consistently use plasma miRNAs in future clinical application [25,[34][35][36][37][38][39][40][41][42][43][44]. Indeed, miRNA profiles and miRNA concentrations were considerably different between serum and plasma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, compared to serum, plasma might retain higher protein levels, including those of coagulant-related proteins. These finding prompt us to consistently use plasma miRNAs in future clinical application [25,[34][35][36][37][38][39][40][41][42][43][44]. Indeed, miRNA profiles and miRNA concentrations were considerably different between serum and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Next, 11 miRNAs previously reported as biomarkers in body fluids were excluded. We limited the target miRNAs to oncogenic miRNAs, as previous studies have revealed that high plasma levels of oncogenic miRNAs might be derived from tumor necrosis, apoptosis and the active release of secretory vesicles, such as exosomes, from cancer cells; thus, these miRNAs in plasma could reflect tumor dynamics in cancer tissues [34][35][40][41]. Tumorsuppressive miRNAs and functionally unknown miRNAs were excluded in the present study because the origin of these miRNAs is not well known [38].…”
Section: Selection Of Candidate Mirnas From the Ncbi Databasementioning
confidence: 99%
See 2 more Smart Citations
“…Enormous efforts have been made to identify the special molecular markers for PDAC, which show vast application prospect as targets for the disease treatment. The research fields of molecular markers for PDAC include proteins, such as K-Ras, p16, and SMAD4 (3)(4)(5); miRNAs, such as miR-210 and miR-221 (6)(7)(8); and the recently research hotspot the lncRNAs.…”
Section: Introductionmentioning
confidence: 99%